Structure determination of the intermediate tin oxide Sn304 by precession electron diffraction - White, Thomas A. (2010)
The structure of an intermediate form of tin oxide was investigated by precession electron diffraction. The results support a revised version of a layered, vacancy-ordered structure for Sn304 proposed in the preceding literature. The lattice parameters were found to be consistent with a monoclinic cell which is a distorted superlattice of the cassiterite structure. Zero-order Laue zone (ZOLZ) Patterson maps, phased projections and phases measured from a [001] first-order Laue zone (FOLZ) conditional Patterson map all support the proposed modification to the tin coordinates over the unmodified form. The results of kinematical refinement were not satisfactory, although weak features found in the Patterson maps were consistent with the oxygen atoms being located close to the previously proposed positions.